PENGARUH MOTIVASI, LINGKUNGAN KERJA DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN DI GRAND CEMARA HOTEL - Pamuji Gesang Raharjo; Adittia Rusdiansyah (LPPM Universitas Asa Indonesia, 2018)
Purpose- The purpose of this study was to determine the effect of motivation, work environment, and job satisfaction on employee performance at Grand Cemara Hotel. Design/methology/approach- The survey was conducted on 60 respondents, namely all employees of Grand Cemara Hotel. The method used is quantitative descriptive. Findings- The results found that partially independent variables (motivation, work environment, and job satisfaction) affect the dependent variable (employee performance) with a significance limit of 0.05 so that it can be concluded that motivation, work environment, and job satisfaction have a significant effect on employee performance. While by simultaneous, the influence of motivation, work environment, and job satisfaction on employee performance is 47.9%.